ANALISIS KEPUASAN PELANGGAN PERSPEKTIF ISLAM PADA TOKO BUSANA MUSLIM RABBANI DI KOTA BANDA ACEH - Yusniar Yusniar (AL-ILMU, 2023)
This study aims to analyze the variables that influence consumer satisfaction at the Rabbani Gallery Banda Aceh Muslim fashion store. This research is a quantitative research, where the samples taken were 100 respondents, namely all consumers of the Rabbani Gallery Banda Aceh store using a purposive sampling technique. The type of data used is primary data, namely distributing questionnaires through the Google form. The research analysis method was carried out using multiple linear regression. Research finds that brand image and product quality simultaneously and partially have a positive and significant effect on consumer satisfaction. Based on the R2 test, the influence exerted by the independent variables on the dependent variable was 36.0% while the remaining 64.0% was influenced by other variables not included in this study. Keywords: Brand Image, Product Quality, Satisfaction, Perspective and Islam